PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, LINGKUNGAN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA GURU - Suyatno, Sugeng (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This study aims to determine the influence of principal leadership and work environment on teacher’s work motivation in SDN 23 Pulau Rimau, and the influence of headmaster leadership, work environment and work motivation on teacher performance. The research uses quantitative approach and path analysis technique. The population in this study is all teachers in SDN 23 Pulau Rimau as many as 13 respondents. The results of this study indicate the principal’s leadership and work environment have a partial effect in teachers ‘work motivation, meaning that the principal’s leadership and work environment have a direct influence on Teachers’ work motivation. Since the leadership of principal has a partial effect on Teacher performance, it can be stated that the principal’s leadership has a direct effect on teacher performance. Furthermore, since work motivation has no effect on Teacher performance, the leadership of principal and the work environment does not have an indirect effect on Teacher